“Since You’re So Rich, You Must Be Really Smart”: Talent, Rent Sharing, and the Finance Wage Premium - Böhm, Michael J; Metzger, Daniel; Strömberg, Per (Review of Economic Studies, 2023)
Abstract Financial sector wages have increased extraordinarily over the last decades. We address two potential explanations for this increase: (1) rising demand for talent and (2) firms sharing rents with their employees. Matching administrative data of Swedish workers, which include unique measures of individual talent, with financial information on their employers, we find no evidence that talent in finance improved, neither on average nor at the top. The increase in relative finance wages is present across talent and education levels, which together can explain at most 20% of it. In contrast, rising financial sector profits that are shared with employees account for up to half of the relative wage increase. The limited labour supply response may partly be explained by the importance of early-career entry and social connections in finance. Our findings alleviate concerns about “brain drain” into finance but suggest that finance workers have captured rising rents over time.